Pontas de pulverização e taxas de aplicação sobre o controle da ferrugem asiática em diferentes cultivares de soja - Favera, Diego Dalla (2012)
The suitability of application technology, particularly with regard to spray nozzles and spray rates to the target characteristics, mainly related to plant architecture, can improve the quality of the deposition of fungicides, which in turn can maximize efficiency of asian rust control and soybean yield. This study aimed to evaluate the control of the asian rust and yield of soybean due to the application of fungicides with different spray nozzles and spray rates on cultivars with different plant architectures. For this purpose an experiment was conducted in Itaara - RS, in a randomized block design with split plots and two of the factors arranged in bands. The first factor (cultivars) were arranged in bands on the main plots. The second factor (nozzles) was placed in bands in the subplots and the third factor (spray rates) were randomized within subsubplots. Were used four replications (blocks). Were used soybean cultivars A 6411 RG, BMX Apollo RR, TMG 4001 RR, A 7636 RG and BMX Potência RR. As a second factor, were used the spray nozzles XR11001, TJ-6011002 and TXA800067 and as the third factor application rates 70, 100 and 130 L.ha-1, plus a control without application. There were two applications of fungicides. The parameters evaluated were leaf area index (LAI) stratified by thirds of the canopy, the percentage of luminance within the lower and middle thirds of the canopy, the percentage of canopy closure, the number of branches.m-2, height plant, the shape of leaves, the relative chlorophyll content in the three thirds of the canopy, the density, DMV, homogeneity and relative amplitude of the drops, the severity of the asian rust and yield and thousand grain weight stratified in three thirds canopy. The results indicate the need for parameters spray nozzles and spray rates are adjusted to the plant architecture of the cultivars, especially the leaf area index (LAI) and plant height.